A STUDY ON EMPLOYEE ENGAGEMENT WITH SPECIAL REFERENCE TO ANCILLARY INDUSTRY OF BHEL, TIRUCHIRAPALLI - Daisy, B.Asha; Suresh, C. (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of the study is to find out the employee engagement in the Ancillary Industry of BHEL at Tiruchirapalli. The study has been carried out on employees of Ancillary Industry of BHEL. In this study descriptive design and simple random sampling was used. The population size was 250. The sample size was 120. The primary data was taken with the help of questionnaire for the study. Statistical analysis of chi – square and correlation analysis was used in this study. It is found that the respondents were strongly agreed that they are allotted by sufficient tools and resources to do their tasks. It is also found that there is positive correlation between the experience of respondents and opinion about compensates the work fairly and equally.